Alienation, Adoption or Adaptation? Aestheticist Paintings by Women - Pamela Gerrish Nunn (Cahiers Victoriens et Edouardiens)
In scrutinising Aestheticism, feminist scholarship has found the usual characteristics: a band of male actors, achievers and heroes, an extensive use of female imagery, and an investment in the idea or fantasy of Woman in the absence (designed or accidental) of actual women. With regard to Aestheticism as a literary trend, scholars working under the influence of feminism, from Elaine Showalter on, have restored female agency to the territory, re-instating the achievements of various women writers in shaping Aestheticism in its own time, while provoking a reassessment of its meanings and messages through this problematising of the authority of its traditional movers and shakers (Schaffer and Psomiades, Women and British Aestheticism, 1999; Schaffer, The Forgotten Female Aesthetes, 2000). The same has not occurred for the visual art of Aestheticism.To address the work of gender within Aestheticism, this paper proposes some specific works by women artists as characteristic of the style. In so doing it introduces several new names (Isobel Gloag, Constance Halford, Thea Proctor) into the cast of executive characters that the author contends are necessary to a full account of Aestheticism as a trend in British culture bridging the 19th and 20th centuries.